SOSIALISAI IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI SMP AL-AMIN TOBA SEKAMPUNG LAMPUNG TIMUR - Yacub, Jamiluddin; Ardiansyah, Ahmad; Damanhuri, Damanhuri (LPPM STAI DARUSSALAM LAMPUNG, 2023)
The aim of holding a socialization on the application of the independent learning curriculum is to provide an overview of science to Al-Amin Toba Middle School teachers so that they better understand the application of the independent curriculum. curriculum initiated by the Ministry of Education and Culture. This activity was attended by Al-Amin Middle School teachers. The methods and forms of community service activities are training, presentations and coaching, with varied lecture techniques accompanied by discussions and questions and answers, as well as assignments. The results of this service resulted in an increase in participants' understanding of the Independent Curriculum. Teachers' understanding of each activity material is in the sufficient category with a percentage of 13.3%. In the good category the percentage is 33.3% and in the very good category the percentage is 53.4%. Socialization and assistance in creating teaching modules for Al-Amin Middle School also shows that teachers have the ability to develop teaching modules. The contribution of community service is to provide an understanding of the Independent Curriculum as an effort to improve the quality of education in Indonesia in accordance with the needs of the times so that students are not only made to be intelligent. However, it also has a character that is in accordance with Pancasila values ​​or what is called the Pancasila Student Profile form